Chain-gang all-stars [large type] - Adjei-Brenyah, Nana Kwame (Center Point Large Print, 2023)
"Loretta Thurwar and Hamara "Hurricane Staxxx" Stacker are the stars of Chain-Gang All-Stars, the cornerstone of CAPE, or Criminal Action Penal Entertainment, a highly popular, highly controversial, profit-raising program in America's increasingly dominant private prison industry. It's the return of the ancient gladiator games, and prisoners are competing for the ultimate prize: their freedom. In CAPE, prisoners travel as Links in Chain-Gangs, competing in death-matches for packed arenas with righteous protestors at the gates. Thurwar and Staxxx, both teammates and lovers, are the fan favorites. And if all goes well, Thurwar will be free in just a few matches, a fact she carries as heavily as her lethal hammer. As she prepares to leave her fellow Links, she considers how she might help preserve their humanity, in defiance of these so-called games, but CAPE's corporate owners will stop at nothing to protect their status quo, and the obstacles they lay in Thurwar's path have devastating consequences" -- Back cover.